Clade IIb Mpox virus (MPXV) vertical transmission and fetal demise in a pregnant rhesus macaque model - Nicholas P. Krabbe; Ann M. Mitzey; Saswati Bhattacharya; Elaina R. Razo; Xiankun Zeng; Nell Bekiares; Amy Moy; Amy Kamholz; Julie A. Karl; Gregory Daggett; Grace VanSleet; Terry Morgan; et al. (PLoS ONE, 2025)
Infection with clade I Mpox virus (MPXV) results in adverse pregnancy outcomes, yet the potential for vertical transmission resulting in fetal harm with clade IIb MPXV, the clade that is currently circulating in the Western Hemisphere, remains unknown. We sought to establish a pregnant rhesus macaque model of clade IIb MPXV infection with early gestation inoculation to understand if infection results in vertical transmission and adverse pregnancy outcomes. Three pregnant rhesus macaques were inoculated intradermally with 1.5 x 105 plaque forming units (PFU) of clade IIb MPXV near gestational day (GD) 30 and animals were monitored for viremia and maternal and fetal well-being. Animals were euthanized to collect tissues at 5, 14, or 25 days post-inoculation (dpi). Tissues were evaluated for viral DNA (vDNA) loads, infectious virus titers, histopathology, MPXV mRNA and protein localization, as well as MPXV protein co-localization with placental cells including, Hofbauer cells, mesenchymal stromal cells, endothelial cells, and trophoblasts. vDNA was detected in maternal blood and skin lesions by 5 dpi. Lack of fetal heartbeat was observed at 14 or 25 dpi for two dams indicating fetal demise; the third dam developed significant vaginal bleeding at 5 dpi and was deemed an impending miscarriage. vDNA was detected in placental and fetal tissue in both fetal demise cases. MPXV localized to placental villi by ISH and IHC. Clade IIb MPXV infection in pregnant rhesus macaques results in vertical transmission to the fetus and adverse pregnancy outcomes, like clade I MPXV. This suggests that clade IIb MPXV infection in human pregnancy poses a danger to maternal and fetal health as well. Further studies are needed to determine whether antiviral therapy with tecovirimat will prevent vertical transmission and improve pregnancy outcomes.